Human factors affecting the hydrological characteristics of the waters of the Euphrates River since the entry of the Hindiya Dam into the Kufa Dam - Al-Hasnawi, Mariam Ali Hussein; AlIbrahimi, Suhaila Najem (Al-Adab Journal, 2023)
The study aims to identify the impact of human factors on the hydrological and environmental characteristics. The study area is determined by the course of the Euphrates River from the Hindiya dam to the Kufa dam, which is determined astronomically between two latitudes (32º43'25" - 32º10'14") north and longitudes (44º24'33" - 44º5'8") east.The human factors represented by the Euphrates River water uses (domestic and agricultural uses), human waste, control and storage projects, showed that the population of the study area depend on the Euphrates River water for domestic uses, and that agricultural lands depend primarily on the Euphrates River water that penetrates its lands. Agricultural use is one of the largest Uses in terms of its consumption of water and affects the hydrological characteristics such as the discharge, the level and the chemical properties of the water due to the wastes it raises such as salts, industrial and organic pollutants and sewage water, the greatest impact on the high concentrations of pollutants in the river water.